Sweden and the question of Poland’s independence (1914–1918) - Piotrowski, Bernard (Folia Scandinavica Posnaniensia, 2007)
The author claims that the question of Poland’s independence was of great political interest to the Swedes of World War I, especially to Swedish activists who collaborated with Germany. The Polish question was seen in the wider context of aspiration of the Baltic “oppressed peoples”. A number of eminent Swedes openiy demanded that the right to independent state existence be granted to Poland. The author also discusses the role of various organizations (e.g. the League of Peoples Oppressed by Russia and Information Office “Polonia”) active in Stockholm at that time.